The solutions are: x = -5, 2 ;
which are Answer choices: [E] and [F] .
_________________________________________________
Given:
_________________________
x² + 4x − 9 = x + 1 ;
___________________________
Simplify, by subtracting "x" and "1" from EACH SIDE of the equation:
______________________________________________________
x² + 4x − 9 − x − 1 = x + 1 − x − 1 ;
__________________________________________
to get:
___________________________________________________
x² + 3x − 10 = 0 ;
________________________
Now, we can factor the left-hand side of the equation:
____________________________________________
x² + 3x − 10 = (x + 5) (x − 2); and rewrite the equation as:
________________________________________________
(x + 5) (x − 2) = 0 ;
________________________________________________
The solutions are: x = -5, 2 ;
which are Answer choices: [E] and [F] .
_________________________________________________